Obstacles To Gaining A Competitive Advantage In The Branches Of Commercial Banks Operating In The City Of Nasiriyah - Wafaa Chitheer Mezaal, Wafaa (University of Thi-Qar Journal, 2022)
The concept of competitive advantage in terms of meaning refers to the characteristics that distinguish the organization from other competing organizations and achieve a strong position towards the different parties. Research to shed light on the most prominent internal and external obstacles that limit the acquisition of competitive advantage by applying to a sample of commercial banks operating in the city of Nasiriya to identify these obstacles and find appropriate solutions to them, by relying on a questionnaire distributed to the members of the research sample to obtain the most important data related to the research, and using the program The statistician (SPSS) analyzed these data to reach the required results and then develop the necessary solutions and proposals for this, enabling bank departments to gain competitive advantage, growth, survival and continuity in the labor market, which only recognizes the superior.